The Effectiveness of Giving Various Planting Media to the Floating Raft Aquaponics System on the Growth of Shallots - Devi Andriani Luta; Maimunah Siregar (International Forum of Researchers and Lecturers, 2023)
Aquaponics consists of fish farming and plant maintenance. Water, which is a medium for fish cultivation, is used as a source of nutrition in plant maintenance, while plants function as a biofilter for water. This study used red onion seeds of the Sanren variety. This study was an experimental study using a non-factorial randomized block design (RBD) consisting of 1 treatment factor and 5 blocks. to get 20 research plots. Planting Media Factor with a symbol (M) which consists of 4 levels, namely: M1: Compost, M2: Chaff Charcoal, M3: Cocopeat, M4: Rice Husk. The results showed that the use of several growing media in the floating raft aquaponic system had a very significant effect on plant height (cm) and the number of leaves (strands).